SPATIAL TAX INTELLIGENCE: IMPLEMENTING INTEGRATED SPATIAL DECISION SUPPORT SYSTEMS FOR SMART URBAN GOVERNANCE - Irfana, Wildan R; Bahar, Haldis A; Candra, Muhammad H (Smart City, 2026)
The transition toward smart governance requires local governments to adopt data-driven policy approaches, particularly in managing urban tax capacity. However, tax administration in many developing regions remains predominantly tabular and administrative, limiting the ability to capture the spatial dynamics of economic activities. This reveals a critical knowledge gap, as integrated frameworks combining spatial and tax data to identify geographic disparities in tax performance remain limited. Consequently, areas with high economic activity but low tax compliance, referred to as tax blind spots, often remain undetected. This study aims to analyze the effectiveness of integrating spatial and tax data in identifying spatial-tax mismatches and transforming local tax governance. Using Garut Regency, Indonesia, as a case study, the research examines the spatial distribution of taxable objects, in relation to their compliance status, and identifies areas where economic potential does not correspond with tax contribution. This study employs a mixed-methods approach with a Research and Development (R&D) design by integrating geospatial analysis and system development within a unified workflow. Spatial and tax data are consolidated through data integration and preprocessing, followed by spatial analysis to identify patterns of compliance and detect under-taxed areas. The processed data are then deployed within a web-based geospatial platform, enabling real-time access and interactive mapping. The analytical outputs are operationalized through an interactive dashboard that integrates spatial and tax indicators into a user-centered decision-support interface. The results show that geo-visual analytics effectively reveals tax blind spots, improves tax potential mapping, and enhances the identification of unregistered taxable objects. The novelty lies in the operationalization of Spatial Tax Intelligence as an integrated geospatial decision support system that combines real-time data integration, spatial analysis, and interactive visualization to support adaptive, evidence-based tax governance in developing regions.